Electromagnetic wave shielding material, electronic component, and electronic device

CN116761714BActive Publication Date: 2026-10-09FUJIFILM CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202180085067.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-12-15
Filing Date
2021-12-22
Publication Date
2026-10-09
Estimated Expiration
2041-12-22

AI Technical Summary

Benefits of technology

[0027] According to one aspect of the present invention, a novel electromagnetic wave shielding material capable of providing high shielding performance against both electric and magnetic field waves can be provided. Furthermore, according to one aspect of the present invention, an electronic component and electronic device incorporating the electromagnetic wave shielding material can be provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004288836820000041
    Figure BDA0004288836820000041
  • Figure BDA0004288836820000042
    Figure BDA0004288836820000042
  • Figure BDA0004288836820000301
    Figure BDA0004288836820000301
Patent Text Reader

Abstract

Provided is an electromagnetic wave shielding material, an electronic component including the electromagnetic wave shielding material, and an electronic device. The electromagnetic wave shielding material includes a multilayer structure having an insulating layer, i.e., a high magnetic permeability layer, with a real part of a complex relative magnetic permeability of 30 or more at a frequency of 100 kHz between two metal layers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an electromagnetic wave shielding material, electronic components, and electronic devices. Background Technology

[0002] In recent years, electromagnetic wave shielding materials have attracted attention as materials used to reduce the influence of electromagnetic waves in various electronic components and electronic devices (see, for example, Patent Document 1).

[0003] Previous technical documents

[0004] Patent documents

[0005] Patent Document 1: Japanese Patent Application Publication No. 3-6898 Summary of the Invention

[0006] The technical problem to be solved by the invention

[0007] Electromagnetic wave shielding materials (hereinafter also referred to as "shielding materials") can perform the function of shielding electromagnetic waves by reflecting the electromagnetic waves incident on the shielding material and / or attenuating them inside the shielding material.

[0008] Electromagnetic waves include both electric and magnetic field waves. As an electromagnetic wave shielding material, it is preferred because it can significantly attenuate both electric and magnetic field waves, thus reducing the influence of both in electronic components and electronic devices.

[0009] One objective of this invention is to provide a new electromagnetic wave shielding material that can provide high shielding performance against both electric and magnetic field waves.

[0010] means for solving technical problems

[0011] One aspect of the present invention relates to

[0012] An electromagnetic wave shielding material comprises a multilayer structure having an insulating layer, i.e., a high permeability layer, between two metal layers, having a complex relative permeability real part of 30 or more at a frequency of 100kHz.

[0013] In one embodiment, the aforementioned high permeability layer can contain magnetic particles.

[0014] In one embodiment, the magnetic particles may include metallic particles.

[0015] In one embodiment, the high permeability layer can contain flat-shaped particles as magnetic particles.

[0016] In one approach, the sum of the absolute value of the average value of the orientation angles of the flat-shaped particles relative to the surface of the high permeability layer and the variance of the orientation angles, i.e., the degree of orientation, can be less than 30°.

[0017] In one embodiment, the aforementioned high magnetic permeability layer may contain a resin.

[0018] In one embodiment, the glass transition temperature (Tg) of the resin can be below 50°C.

[0019] In one method, the thickness of one of the two metal layers is set as T1, and the thickness of the other metal layer is set as T2. T1 can be greater than or equal to T2, and the thickness ratio (T2 / T1) can be 0.15 or greater.

[0020] In one embodiment, one or both of the two metal layers are metal layers containing 80.0% by mass or more of a metal selected from the group consisting of Al and Mg.

[0021] In one embodiment, the electromagnetic wave shielding material may further include one or more layers selected from the group consisting of an adhesive layer and a bonding layer.

[0022] In one embodiment, the total thickness of the metal layers contained in the electromagnetic wave shielding material is less than 100 μm.

[0023] In one embodiment, the total thickness of the electromagnetic wave shielding material can be less than 200 μm.

[0024] One aspect of the present invention relates to an electronic component comprising the aforementioned electromagnetic wave shielding material.

[0025] One aspect of the present invention relates to an electronic device comprising the aforementioned electromagnetic wave shielding material.

[0026] Invention Effects

[0027] According to one aspect of the present invention, a novel electromagnetic wave shielding material capable of providing high shielding performance against both electric and magnetic field waves can be provided. Furthermore, according to one aspect of the present invention, an electronic component and electronic device incorporating the electromagnetic wave shielding material can be provided. Detailed Implementation

[0028] Electromagnetic wave shielding materials

[0029] One aspect of the present invention relates to an electromagnetic wave shielding material comprising a multilayer structure having an insulating layer, i.e., a high permeability layer, between two metal layers having a complex relative permeability real part of 30 or more at a frequency of 100 kHz.

[0030] In this invention and specification, "electromagnetic wave shielding material" refers to a material capable of exhibiting shielding performance against electromagnetic waves of at least one frequency or at least a portion of a frequency band. "Electromagnetic waves" are divided into electric field waves and magnetic field waves. Preferably, the "electromagnetic wave shielding material" is a material capable of exhibiting shielding performance against either electric field waves of at least one frequency or at least a portion of a frequency band, or magnetic field waves of at least one frequency or at least a portion of a frequency band. More preferably, it is a material capable of exhibiting shielding performance against both electric field waves and magnetic field waves with a wider frequency band. The higher the shielding performance, the more preferred the material.

[0031] When measuring complex relative permeability using a permeability measuring device, a real part μ' and an imaginary part μ' are typically displayed. In this invention and this specification, the real part of the complex relative permeability refers to this real part μ'. Hereinafter, the real part of the complex relative permeability at a frequency of 100 kHz will also be simply referred to as "permeability". Permeability can be measured using commercially available permeability measuring devices or permeability measuring devices with known structures.

[0032] In this invention and specification, "insulation" means conductivity less than 1 S (Siemens) / m. The conductivity of a layer is calculated based on its surface resistivity and thickness using the following formula. Conductivity can be measured using known methods.

[0033] Conductivity [S / m] = 1 / (Surface resistivity [Ω] × Thickness [m])

[0034] The thickness (total thickness) of the electromagnetic wave shielding material and the thickness of each layer contained in the electromagnetic wave shielding material are obtained by taking a cross-section exposed by a known method using a scanning electron microscope (SEM) and calculating the thickness as the arithmetic mean of the thickness at 5 randomly selected locations in the obtained SEM image.

[0035] In this invention and specification, "metal layer" refers to a layer containing metal. A metal layer can be a layer containing one or more metals, such as a pure metal composed of a single metallic element, an alloy of two or more metallic elements, or an alloy of one or more metallic elements and one or more non-metallic elements. Details regarding metal layers will be described later.

[0036] Regarding the reasons why the aforementioned electromagnetic wave shielding materials can exhibit high shielding performance against both electric and magnetic field waves, the inventors make the following conjectures. However, the present invention is not limited to the conjectures described in this specification.

[0037] The propagation constant γ and characteristic impedance Zs of a material when an electromagnetic wave is incident on it can be expressed by the following formula. In the formula, j is the imaginary unit, ω is the angular frequency of the electromagnetic wave [1 / s], μ is the permeability of the material [H / m], σ is the conductivity of the material [S / m], and ε is the dielectric constant of the material [F / m].

[0038] [Formula 1]

[0039]

[0040]

[0041] The propagation constant γ is related to the amplitude attenuation of electromagnetic waves in a material; the larger γ is, the greater the attenuation of the electromagnetic wave amplitude. Comparing the metal layer with the aforementioned high permeability layer, σ is very large in the metal layer, therefore γ is also large. Thus, a large attenuation of electromagnetic waves can be expected within the metal layer. Conversely, in the aforementioned high permeability layer, γ is large due to the large μ. Therefore, attenuation of electromagnetic waves can be expected within the high permeability layer. On the other hand, in materials with small μ, σ, and ε, such as air and resin, the attenuation of electromagnetic waves within the material is very small.

[0042] Furthermore, the characteristic impedance Zs is related to the reflectivity and transmittance when an electromagnetic wave is incident on the boundary of a material and exits from the boundary. The greater the difference between the wave impedance and the characteristic impedance of the electromagnetic wave, the greater the reflection at the material boundary. In a metallic layer, the characteristic impedance decreases because σ is large and μ is small. Conversely, in the aforementioned high permeability layer, σ decreases because μ is large, and the characteristic impedance increases.

[0043] At a sufficiently far distance from the wave source (e.g., about 1 / 6 of the wavelength of the electromagnetic wave), the electromagnetic wave becomes a plane wave with a wave impedance of approximately 377 Ω. On the other hand, at a sufficiently close distance from the wave source (e.g., closer than 1 / 6 of the wavelength of the electromagnetic wave), the wave impedance decreases as the source approaches the source when the source is a small loop current (so-called magnetic field wave), and increases as the source approaches the source when the source is a small dipole (so-called electric field wave).

[0044] In the KEC method, a representative method for measuring shielding performance, according to the "Equivalent Circuit of Lumped Constant for Electric / Magnetic Field Shielding Effect Measuring Instrument (KEC Method)" (Technical Report of the Imaging Information Media Society, Vol. 25.30 (2001)), in the case of magnetic field waves, the fluctuation impedance at 100kHz is 0.0033, which is very small compared to the fluctuation impedance of 377 for plane waves. Furthermore, KEC is the abbreviation for the Kansai Electronics Industry Promotion Center.

[0045] Thus, because the wave impedance of the magnetic field wave is small, when the magnetic field wave is incident on a metal layer with low characteristic impedance and exits, the reflectivity at the interface is small due to the small difference between the wave impedance and the characteristic impedance. On the other hand, when the magnetic field wave is incident on the aforementioned high permeability layer with high characteristic impedance and exits, the reflectivity at the interface becomes higher than that of the metal layer because of the large difference between the wave impedance and the characteristic impedance.

[0046] To achieve high shielding performance for electromagnetic waves in electromagnetic wave shielding materials, in addition to improving the attenuation capability of electromagnetic waves, it is preferable to increase reflection at the interface. That is, it is preferable to significantly attenuate electromagnetic waves by repeatedly reflecting them at the interface and passing through the shielding material multiple times. However, as mentioned above, regarding the actions of the metal layer and the aforementioned high permeability layer on electromagnetic waves, it can be said that although the metal layer has a high electromagnetic wave attenuation capability, it has a low reflection of magnetic field waves at the interface, while the aforementioned high permeability layer has a lower electromagnetic wave attenuation capability than the metal layer, it has a higher reflection of magnetic field waves at the interface. Therefore, in either a single metal layer or a single aforementioned high permeability layer, it is difficult to simultaneously achieve high reflection and attenuation for magnetic field waves.

[0047] In contrast, the aforementioned electromagnetic wave shielding material, through its multilayer structure containing a high-permeability layer between two metal layers, can simultaneously mitigate the reflection of electromagnetic waves at the interface and the attenuation of electromagnetic waves within the layers. The inventors believe this is the reason why the aforementioned electromagnetic wave shielding material can exhibit high shielding performance against both electric and magnetic field waves.

[0048] The following is a more detailed explanation of the aforementioned electromagnetic wave shielding materials.

[0049] <High permeability layer>

[0050] The permeability (real part of complex relative permeability at 100kHz) of the aforementioned high-permeability layer is 30 or higher. Including an insulating layer with a high permeability of 30 or higher between the two metal layers helps the electromagnetic wave shielding material exhibit high shielding performance against both electric and magnetic field waves. From this perspective, the permeability is preferably 40 or higher, more preferably 50 or higher, further preferably 60 or higher, even more preferably 70 or higher, further more preferably 80 or higher, even more preferably 90 or higher, and even more preferably 100 or higher. Furthermore, the permeability can be, for example, 200 or lower, 190 or lower, 180 or lower, 170 or lower, or 160 or lower, or higher than the values ​​exemplified here. The higher the permeability, the larger the characteristic impedance Zs becomes, resulting in a higher interface reflection effect, and therefore this is preferable.

[0051] The aforementioned high permeability layer is an insulating layer. This also helps the electromagnetic wave shielding material to exhibit high shielding performance against magnetic field waves in addition to electric field waves. The conductivity of the aforementioned high permeability layer is less than 1 S / m, preferably less than 0.5 S / m, more preferably less than 0.1 S / m, and even more preferably less than 0.05 S / m. The conductivity of the aforementioned high permeability layer can, for example, be 1.0 × 10⁻⁶. -12 S / m or higher or 1.0×10 -10 S / m or higher.

[0052] (Magnetic particles)

[0053] The aforementioned high permeability layer can contain magnetic particles. In this invention and specification, "magnetic" refers to ferromagnetic property. As magnetic particles, one type selected from the group consisting of magnetic particles commonly referred to as soft magnetic particles, such as metal particles and ferrite particles, or a combination of two or more types can be used. Metal particles generally have about 2 to 3 times the saturation magnetic flux density compared to ferrite particles, thus maintaining permeability even under strong magnetic fields without magnetic saturation, and exhibiting shielding performance. Therefore, the magnetic particles contained in the high permeability layer are preferably metal particles.

[0054] metal particles

[0055] In this invention and specification, "metal particles" include pure metal particles composed of a single metallic element, and particles of alloys of one or more metallic elements with one or more other metallic elements and / or non-metallic elements. The presence or absence of crystallinity is irrelevant to the metal particles. That is, metal particles can be crystalline or amorphous. Examples of metallic or non-metallic elements included in metal particles include Ni, Fe, Co, Mo, Cr, Al, Si, B, and P. Metal particles may contain components other than the constituent elements of metals (including alloys), or they may not contain any of these components. In addition to the constituent elements of metals (including alloys), metal particles may also contain elements contained in additives that can be added at any rate and / or elements contained in impurities that may be unintentionally introduced during the manufacturing process of the metal particles. In the metal particles, the content of the constituent elements of the metal (including alloys) is preferably 90.0% by mass or more, more preferably 95.0% by mass or more, and may be 100% by mass, less than 100% by mass, less than 99.9% by mass, or less than 99.0% by mass.

[0056] Examples of metallic particles include iron-silicon-aluminum alloys (Fe-Si-Al alloys), permalloy (Fe-Ni alloys), molybdenum-permalloy (Fe-Ni-Mo alloys), Fe-Si alloys, Fe-Cr alloys, Fe-containing alloys commonly referred to as iron-based amorphous alloys, Co-containing alloys commonly referred to as cobalt-based amorphous alloys, alloys commonly referred to as nanocrystalline alloys, iron, and permendur (Fe-Co alloys). Among these, iron-silicon-aluminum alloys exhibit high saturation magnetic flux density and permeability, and are therefore preferred.

[0057] Flat-shaped particles

[0058] From the viewpoint of forming a layer exhibiting high magnetic permeability as a high magnetic permeability layer, the aforementioned magnetic particles are preferably particles with a flat shape (flat-shaped particles). By arranging the long side direction of the flat-shaped particles to be more nearly parallel to the in-plane direction of the high magnetic permeability layer, the long side direction of the particles is further aligned with the vibration direction of electromagnetic waves orthogonally incident on the electromagnetic wave shielding material, thereby reducing the reverse magnetic field and thus obtaining higher magnetic permeability. In this invention and this specification, "flat-shaped particles" refers to particles with an aspect ratio of 0.20 or less. The aspect ratio of the flat-shaped particles is preferably 0.15 or less, more preferably 0.10 or less. The aspect ratio of the flat-shaped particles can, for example, be 0.01 or more, 0.02 or more, or 0.03 or more. For example, by performing flattening processing using known methods, the shape of the particles can be set to a flat shape. Regarding the flattening process, for example, refer to the description in Japanese Patent Application Publication No. 2018-131640, specifically paragraphs 0016 and 0017 and the description in the embodiments of Japanese Patent Application Publication No. 2018-131640. The magnetic particles contained in the high permeability layer are preferably flattened particles of an iron-silicon-aluminum alloy.

[0059] As described above, from the viewpoint of forming a layer exhibiting high magnetic permeability, it is preferable to arrange the long side direction of the flat-shaped particles to be more parallel to the in-plane direction of the high magnetic permeability layer. From this perspective, the sum of the absolute value of the average value of the orientation angles of the flat-shaped particles relative to the surface of the high magnetic permeability layer and the variance of the orientation angles, i.e., the degree of orientation, is preferably 30° or less, more preferably 25° or less, further preferably 20° or less, and even more preferably 15° or less. The degree of orientation can, for example, be 3° or more, 5° or more, or 10° or more, or even lower than the values ​​illustrated here. Methods for controlling the degree of orientation will be described later.

[0060] In this invention and this specification, the aspect ratio and orientation degree of the magnetic particles are determined by the following method.

[0061] The profile of the high permeability layer was exposed using a known method. Images of this profile, taken from randomly selected areas, were obtained as SEM images. The imaging conditions were set to an accelerating voltage of 2 kV and a magnification of 1000x, yielding SEM images as reflected electron images.

[0062] Using the `cv2.imread()` function of the OpenCV4 image processing library (manufactured by Intel Corporation), the second argument is set to 0 to read the image in grayscale. The midpoint between the high-brightness and low-brightness regions is used as the boundary. The `cv2.threshold()` function is then used to obtain a binarized image. The white areas (high-brightness areas) in the binarized image are identified as magnetic particles.

[0063] For the obtained binarized image, the externally circumscribed rectangle corresponding to the local area of ​​each magnetic particle is obtained using the cv2.minAreaRect() function. The long side length, short side length, and rotation angle are calculated as the return value of the cv2.minAreaRect() function. When calculating the total number of magnetic particles contained in the binarized image, particles in which only a portion of the particle is included in the binarized image are also included. For particles in which only a portion of the particle is included in the binarized image, the long side length, short side length, and rotation angle are calculated for the portion included in the binarized image. The ratio of the short side length to the long side length (short side length / long side length) is thus used as the aspect ratio of each magnetic particle. In this invention and specification, if, relative to the total number of magnetic particles contained in the binarized image, the aspect ratio is 0.20 or less and the number of magnetic particles defined as flat-shaped particles is 10% or more, the high permeability layer is determined to be a "high permeability layer containing flat-shaped particles as magnetic particles". Furthermore, from the rotation angle obtained above, the "orientation angle" is obtained as the rotation angle relative to the horizontal plane (the surface of the high permeability layer).

[0064] Particles with an aspect ratio of 0.20 or less obtained from the binarized image are identified as flat-shaped particles. The absolute value and variance of the mean (arithmetic mean) of the orientation angles of all flat-shaped particles contained in the binarized image are calculated. This sum is used as the "orientation degree". Furthermore, the coordinates of the circumscribed rectangle are calculated using the cv2.boxPoints() function, and an image is created by rotating the circumscribed rectangle to coincide with the original image using the cv2.drawContours() function. Rotated circumscribed rectangles with obvious false detections are excluded from the aspect ratio and orientation degree calculations. The average (arithmetic mean) of the aspect ratios of the particles identified as flat-shaped particles is used as the aspect ratio of the flat-shaped particles contained in the high permeability layer of the measurement object. This aspect ratio is 0.20 or less, preferably 0.15 or less, and more preferably 0.10 or less. The aspect ratio can be, for example, 0.01 or more, 0.02 or more, or 0.03 or more.

[0065] Relative to the total mass of the high permeability layer, the content of magnetic particles in the high permeability layer can be, for example, 50% or more by mass, 60% or more by mass, 70% or more by mass, 72% or more by mass, 75% or more by mass, or 80% or more by mass, and can be, for example, less than 100% by mass, less than 98% by mass, or less than 95% by mass.

[0066] In one approach, a sintered body (ferrite plate) of ferrite particles can be used as a high permeability layer. Considering that electromagnetic wave shielding materials are sometimes cut to a desired size or sometimes bent into a desired shape, a resin-containing layer is preferred over a ferrite plate as a sintered body as a high permeability layer.

[0067] (resin)

[0068] The high permeability layer can be a layer containing resin, or a layer containing magnetic particles and resin. In a high permeability layer containing magnetic particles and resin, the resin content in every 100 parts by mass of magnetic particles can be, for example, more than 1 part by mass, more than 3 parts by mass, or more than 5 parts by mass, and can also be less than 20 parts by mass or less than 15 parts by mass.

[0069] Resin can act as an adhesive in a high-permeability layer. In this invention and specification, "resin" refers to a polymer, including rubber and elastomers. Polymers include homopolymers and copolymers. Rubber includes natural rubber and synthetic rubber. Furthermore, an elastomer is a polymer that exhibits elastic deformation. Examples of resins include conventionally known thermoplastic resins, thermosetting resins, UV-curable resins, radiation-curable resins, rubber-based materials, and elastomers. Specific examples include polyester resins, polyethylene resins, polyvinyl chloride resins, polyvinyl butyral resins, polyurethane resins, cellulose resins, ABS (acrylonitrile-butadiene-styrene) resins, nitrile-butadiene rubbers, styrene-butadiene rubbers, epoxy resins, phenolic resins, amide resins, styrene-based elastomers, olefin-based elastomers, vinyl chloride-based elastomers, polyester-based elastomers, polyamide-based elastomers, polyurethane-based elastomers, and acrylic elastomers.

[0070] The aforementioned electromagnetic wave shielding material can be bent into any shape for use. If the high permeability layer breaks when the shielding material is bent, the shielding performance may decrease at the breakage point. Therefore, a high permeability layer with excellent fracture resistance and resistance to breakage during bending is preferred. From the viewpoint of improving the fracture resistance of the high permeability layer, a layer containing a resin with a glass transition temperature (Tg) of 50°C or less is preferred as the high permeability layer. In this invention and specification, the glass transition temperature (Tg) is a temperature determined based on the measurement results of heat flow measurement using a differential scanning calorimeter, and is used as the baseline deviation start temperature of the heat flow during heating. From the viewpoint of further improving the fracture resistance of the high permeability layer, the glass transition temperature (Tg) of the resin contained in the high permeability layer is more preferably 40°C or less, more preferably 30°C or less, even more preferably 20°C or less, more preferably 10°C or less, even more preferably 0°C or less, and even more preferably -10°C or less. The glass transition temperature (Tg) of the resin contained in the high permeability layer can be, for example, above -100°C, above -90°C, or above -80°C.

[0071] In addition to the above-mentioned components, the high magnetic permeability layer may also include one or more known additives such as curing agents, dispersants, stabilizers, and coupling agents in any amount.

[0072] <Metallic Layer>

[0073] The aforementioned electromagnetic wave shielding material includes a high permeability layer between two metal layers. The electromagnetic wave shielding material may include one or more multilayer structures with the high permeability layer between two metal layers, or it may include two or more. That is, the electromagnetic wave shielding material includes at least two metal layers, or it may include three or more metal layers, and it includes at least one high permeability layer, or it may include two or more high permeability layers. The two or more metal layers included in the electromagnetic wave shielding material may have the same composition and thickness in one embodiment, and different compositions and / or thicknesses in another embodiment. Furthermore, when the electromagnetic wave shielding material includes two or more high permeability layers, the two or more high permeability layers may have the same composition and thickness in one embodiment, and different compositions and / or thicknesses in another embodiment.

[0074] Specific examples of the layer structure of the aforementioned electromagnetic wave shielding material include "metal layer / high permeability layer / metal layer", "metal layer / high permeability layer / metal layer / high permeability layer / metal layer", and "metal layer / high permeability layer / metal layer / high permeability layer / metal layer / high permeability layer / metal layer". In the above, the symbol " / " is used to indicate two situations: the layer described on the left side of the symbol and the layer described on the right side are in direct contact without passing through other layers, and they are indirectly stacked through one or more other layers. Specific examples of the other layers mentioned above include double-sided adhesive tape and adhesive used for bonding, as described later.

[0075] As a metal layer, a layer containing one or more metals selected from various pure metals and alloys can be used. The metal layer can exert an attenuation effect in the shielding material. The greater the propagation constant, the greater the attenuation effect; the greater the conductivity, the greater the propagation constant. Therefore, the metal layer preferably contains a metal element with high conductivity. From this perspective, the metal layer preferably contains a pure metal such as Ag, Cu, Au, or Al, or an alloy with any one of these as its main component. A pure metal is a metal composed of a single metallic element and may contain trace amounts of impurities. Generally, a metal composed of a single metallic element with a purity of 99.0% or higher is called a pure metal. Purity is based on mass. Alloys are usually made by adding one or more metallic or non-metallic elements to pure metals to adjust their composition for purposes such as corrosion resistance and increased strength. The main component in an alloy is the component with the highest percentage based on mass, for example, a component that accounts for 80.0% or more (e.g., less than 99.8% by mass) in the alloy. From an economic point of view, it is preferable to use pure metals of Cu or Al or alloys with Cu or Al as the main component. From the point of view of high conductivity, it is more preferable to use pure metals of Cu or alloys with Cu as the main component.

[0076] The purity of the metal in the metal layer, i.e., the metal content, relative to the total mass of the metal layer, can be 99.0% by mass or more, preferably 99.5% by mass or more, and more preferably 99.8% by mass or more. Unless otherwise stated, the metal content in the metal layer refers to the content based on mass. For example, pure metals or alloys processed into sheets can be used as the metal layer. For example, for pure Cu, sheets of various thicknesses (so-called copper foil) are commercially available. For example, this copper foil can be used as the metal layer. Copper foil includes electrolytic copper foil obtained by electroplating to deposit copper foil onto a cathode using its manufacturing method, and rolled copper foil obtained by applying heat and pressure to an ingot to stretch it thinly. Any copper foil can be used as the metal layer of the aforementioned electromagnetic wave shielding material. Furthermore, for example, for Al, sheets of various thicknesses (so-called aluminum foil) are commercially available. For example, this aluminum foil can be used as the metal layer.

[0077] From the perspective of lightweight electromagnetic wave shielding materials, one or both (preferably two) of the two metal layers included in the above-mentioned multilayer structure are preferably metal layers containing metals selected from the group consisting of Al and Mg. This is because the specific gravity divided by the conductivity (specific gravity / conductivity) of Al and Mg are both small. Using metals with smaller values ​​allows for a lighter electromagnetic wave shielding material that achieves high shielding performance. For example, the specific gravity divided by the conductivity (specific gravity / conductivity) of Cu, Al, and Mg, calculated from literature, is as follows: Cu: 1.5 × 10⁻⁶ -7 m / s, Al: 7.6 × 10 -8 m / S, Mg: 7.6 × 10 -8m / s. Based on the above values, from the viewpoint of lightweighting electromagnetic wave shielding materials, Al and Mg are preferred metals. In one embodiment, a metal layer containing a metal selected from the group consisting of Al and Mg can contain only one of Al and Mg, while in another embodiment, it can contain both. From the viewpoint of lightweighting electromagnetic wave shielding materials, one or both metal layers (preferably two layers) of the two metal layers included in the above-mentioned multilayer structure are more preferably metal layers containing a metal selected from the group consisting of Al and Mg with a content of 80.0% by mass or more, and even more preferably metal layers containing a metal selected from the group consisting of Al and Mg with a content of 90.0% by mass or more. A metal layer containing at least Al in Al and Mg can be a metal layer with an Al content of 80.0% by mass or more, or a metal layer with an Al content of 90.0% by mass or more. A metal layer containing at least Mg in Al and Mg can be a metal layer with a Mg content of 80.0% by mass or more, or a metal layer with a Mg content of 90.0% by mass or more. The content of the metals selected from the group consisting of Al and Mg above, the content of Al, and the content of Mg can each be, for example, 99.9% by mass or less. The content of the metals selected from the group consisting of Al and Mg above, the content of Al, and the content of Mg are the contents relative to the total mass of the metal layer.

[0078] Various thicknesses

[0079] From the viewpoint of the processability of the metal layer and the shielding performance of the electromagnetic wave shielding material, regarding the thickness of the metal layer, the thickness of each layer is preferably 4 μm or more, more preferably 5 μm or more, further preferably 10 μm or more, even more preferably 15 μm or more, even more preferably 20 μm or more, and even more preferably 25 μm or more. On the other hand, from the viewpoint of the processability of the metal layer, regarding the thickness of the metal layer, the thickness of each layer is preferably 100 μm or less, more preferably 50 μm or less, even more preferably 45 μm or less, and even more preferably 40 μm or less.

[0080] If the thickness of one metal layer sandwiching a high-permeability layer is defined as T1, and the thickness of the other metal layer is defined as T2, and T1 is greater than or equal to T2 (i.e., T1 = T2 or T1 > T2), then the thickness ratio of the two metal layers (T2 / T1) can be, for example, 0.10 or more. From the viewpoint of exhibiting higher shielding performance against magnetic field waves, it is preferably 0.15 or more, more preferably 0.30 or more, further preferably 0.50 or more, even more preferably 0.70 or more, and even more preferably 0.80 or more. From the viewpoint of exhibiting higher shielding performance against magnetic field waves, the smaller the difference between T1 and T2, the better. The thickness ratio (T2 / T1) can be 1.00 or less, or it can be 1.00 (i.e., T1 = T2). When the electromagnetic wave shielding material comprises two or more multilayer structures having the aforementioned high permeability layer between two metal layers, the ratio of thickness (T2 / T1) described above can be applied to at least one of the aforementioned multilayer structures included in the electromagnetic wave shielding material, or to two or more, or to all of them.

[0081] The shielding material can be bent into any shape depending on the application. If the width of the bend (hereinafter referred to as "bending width") increases when bending the shielding material, the shape of the bend becomes a gentle curve, which may sometimes be difficult to process into the desired shape. From this perspective, a narrower bending width is preferred, for example, preferably 2.20 mm or less, more preferably 2.00 mm or less, and even more preferably 1.50 mm or less. There is a tendency that the thicker the total thickness of the metal layers contained in the shielding material, the wider the bending width. From the viewpoint of narrowing the bending width of the shielding material, the total thickness of the metal layers contained in the electromagnetic wave shielding material is preferably 100 μm or less, more preferably 90 μm or less, more preferably 80 μm or less, even more preferably 70 μm or less, even more preferably 60 μm or less, even more preferably 50 μm or less, and even more preferably 40 μm or less. The total thickness of the metal layers contained in the electromagnetic wave shielding material may be, for example, 8 μm or more or 10 μm or more. The total number of metal layers contained in the electromagnetic wave shielding material is 2 or more, for example, 2 to 5 layers.

[0082] From the viewpoint of the shielding performance of electromagnetic wave shielding materials, regarding the thickness of the aforementioned high permeability layers, the thickness of each layer can be, for example, 3 μm or more, preferably 10 μm or more, and more preferably 20 μm or more. Furthermore, from the viewpoint of the processability of electromagnetic wave shielding materials, the thickness of each of the aforementioned high permeability layers can be, for example, 90 μm or less, preferably 70 μm or less, and more preferably 50 μm or less. When the aforementioned electromagnetic wave shielding material comprises two or more of the aforementioned high permeability layers, the total thickness of the aforementioned high permeability layers included in the electromagnetic wave shielding material can be, for example, 6 μm or more, and, for example, 180 μm or less. The total number of the aforementioned high permeability layers included in the electromagnetic wave shielding material is one or more layers, for example, one to four layers.

[0083] Furthermore, the total thickness of the shielding material can be, for example, 250 μm or less. From the viewpoint of narrowing the aforementioned bending width, a thin total thickness of the shielding material is also preferable. From this perspective, the total thickness of the aforementioned electromagnetic wave shielding material is preferably 200 μm or less, more preferably 190 μm or less, and even more preferably 170 μm or less. The total thickness of the aforementioned electromagnetic wave shielding material can, for example, be 30 μm or more or 40 μm or more.

[0084] <Manufacturing Methods of Electromagnetic Wave Shielding Materials>

[0085] (Methods for forming high magnetic permeability layers)

[0086] The aforementioned high permeability layer can be produced, for example, by drying a coating layer provided with a high permeability layer forming composition. The high permeability layer forming composition includes the components described above and may contain one or more solvents. Examples of solvents include various organic solvents, such as ketone solvents like acetone, methyl ethyl ketone, and cyclohexanone; acetic acid solvents like ethyl acetate, butyl acetate, acetic acid solvents like propylene glycol monomethyl ether acetate and carbiol acetate; solvents like butyl carbitol; aromatic hydrocarbon solvents like toluene and xylene; and amide solvents like dimethylformamide, dimethylacetamide, and N-methylpyrrolidone. One or more solvents, selected considering the solubility of the components used in the preparation of the high permeability layer forming composition, can be mixed in any ratio. The solvent content of the high permeability layer forming composition is not particularly limited and can be determined considering the coatability of the high permeability layer forming composition.

[0087] The composition for forming a high magnetic permeability layer can be prepared by mixing various components sequentially or simultaneously in any order. Furthermore, dispersion can be performed using known dispersers such as ball mills, bead mills, sand mills, and roller mills, and / or mixing can be performed using known mixers such as vibratory mixers, as needed.

[0088] The composition for forming a high magnetic permeability layer can be coated onto a support, for example. Coating can be performed using known coating equipment such as a doctor blade coater or a die coater. Coating can also be performed in a so-called roll-to-roll manner or in batches.

[0089] Examples of supports for forming compositions for coating high permeability layers include films of various resins such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate (PC), polymethyl methacrylate (PMMA), acrylic resins, cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, and polyimide. For details regarding these resin films, please refer to paragraphs 0081 to 0086 of Japanese Patent Application Publication No. 2015-187260. As a support, a support in which the surface (coated surface) of the composition for forming high permeability layers has undergone a peeling treatment by a known method can be used. One method of peeling treatment is forming a release layer. For details regarding release layers, please refer to paragraph 0084 of Japanese Patent Application Publication No. 2015-187260. Furthermore, commercially available resin films that have undergone peeling treatment can also be used as supports. By using a support that has undergone a peeling process on the coated surface, it is possible to easily separate the high permeability layer and the support when the film thickness is high.

[0090] In another approach, the metal layer can be used as a support, and the high permeability layer forming composition can be directly coated onto the metal layer. By directly coating the high permeability layer forming composition onto the metal layer, a laminated structure of the metal layer and the high permeability layer can be manufactured in a single process.

[0091] The coating layer formed by the high permeability layer forming composition can be dried by known methods such as heating or blowing hot air. The drying process can be performed, for example, under conditions that allow the solvent contained in the high permeability layer forming composition to evaporate. As an example, the drying process can be performed for 1 to 2 minutes in a heating atmosphere at a temperature of 80 to 150°C.

[0092] The orientation degree of the flattened particles described above can be controlled by the type of solvent, amount of solvent, liquid viscosity, coating thickness, etc., in the composition for forming a high permeability layer. For example, if the boiling point of the solvent is low, there is a tendency for the orientation degree to increase due to convection caused by drying. If the amount of solvent is small, there is a tendency for the orientation degree to increase due to physical interference between adjacent flattened particles. On the other hand, if the liquid viscosity is low, there is a tendency for the flattened particles to rotate easily, thus decreasing the orientation degree. If the coating thickness is reduced, there is a tendency for the orientation degree to decrease. Furthermore, performing the pressure treatment described later can help reduce the orientation degree. By adjusting the various manufacturing conditions described above, the orientation degree of the flattened particles can be controlled within the range described above.

[0093] (Pressure treatment of high permeability layer)

[0094] High permeability layers can also undergo pressure treatment after film deposition. By applying pressure to a high permeability layer containing magnetic particles, the density of magnetic particles within the high permeability layer can be increased, resulting in higher permeability. Furthermore, high permeability layers containing flattened particles can have their orientation value reduced through pressure treatment, leading to even higher permeability.

[0095] Pressure processing can be performed by applying pressure along the thickness direction of the high magnetic permeability layer using flatbed extruders, roll extruders, etc. A flatbed extruder places the material to be pressurized between two flat extrusion plates arranged vertically, and applies pressure to the material by mechanical or hydraulic pressure combining the two plates. A roll extruder passes the material to be pressurized between rotating pressure rolls arranged vertically, applying mechanical or hydraulic pressure to the rolls, or applying pressure by making the distance between the rolls less than the thickness of the material to be pressurized.

[0096] The pressure during pressurization can be set arbitrarily. For example, in the case of a flatbed extruder, it can be 1 to 50 N (Newtons) / mm. 2 When using a roller extrusion press, for example, the linear pressure is 20–400 N / mm.

[0097] The pressurization time can be set arbitrarily. When using a flatbed extruder, it can be set from 5 seconds to 30 minutes. When using a roller extruder, the pressurization time can be controlled by the conveying speed of the material being pressurized, for example, from 10 cm / min to 200 m / min.

[0098] The materials for the extrusion plates and pressure rollers can be selected from metal, ceramic, plastic, rubber, etc.

[0099] During pressurization, temperature and pressure can be applied to the upper and lower extrusion plates or one side of the extrusion plates of a plate extruder or one side of the upper and lower rolls of a roll extruder. Heating softens the high magnetic permeability layer, thereby achieving a high compression effect when pressure is applied. The heating temperature can be set arbitrarily, for example, between 50°C and 200°C. This heating temperature can be the internal temperature of the extrusion plates or rolls. This temperature can be measured using a thermometer installed inside the extrusion plates or rolls.

[0100] After being heated and pressurized by a plate extruder, the extruded plate can be separated and the high magnetic permeability layer can be extracted, for example, while the extruded plate is at a high temperature. Alternatively, the extruded plate can be cooled by water cooling, air cooling, or other methods while maintaining pressure, and then the extruded plate can be separated and the high magnetic permeability layer can be extracted.

[0101] In a roll extruder, the high magnetic permeability layer can be cooled immediately after extrusion using methods such as water cooling or air cooling.

[0102] It can also be pressurized more than twice.

[0103] When a high permeability layer is formed on a release film, pressure processing can be performed, for example, with the layer stacked on the release film. Alternatively, it can be peeled off from the release film and pressure processed as a single layer of the high permeability layer. When the high permeability layer is formed directly on a metal layer, pressure processing can be performed with the metal layer and the high permeability layer overlapping. Furthermore, by performing pressure processing with the high permeability layer disposed between the metal layers, pressure processing of the high permeability layer and bonding between the metal layer and the high permeability layer can be performed simultaneously.

[0104] (Lamination of the metal layer with the high magnetic permeability layer)

[0105] The metal layer and the high magnetic permeability layer can be directly bonded, for example, by applying pressure and heat. Pressing can be performed using a flatbed extruder, a roll extruder, etc. During the pressing process, the high magnetic permeability layer softens, promoting contact with the surface of the metal layer, thereby enabling adhesion between the metal layer and the high magnetic permeability layer. The pressing pressure can be set arbitrarily. For example, in the case of a flatbed extruder, it can be 1–50 N / mm. 2 When using a roller extruder, the linear pressure is, for example, 20–400 N / mm. The pressing time can be set arbitrarily. When using a flat extruder, it can be, for example, 5 seconds to 30 minutes. When using a roller extruder, the conveying speed of the material being pressed can be controlled, for example, 10 cm / min to 200 m / min. The pressing temperature can be selected arbitrarily, for example, above 50°C and below 200°C.

[0106] Metal layers and high permeability layers can also be used to insert and bond adhesive layers between the metal layer and the magnetic layer.

[0107] In this invention and this specification, "adhesive layer" refers to a layer that has adhesiveness on its surface at room temperature. Here, "room temperature" refers to 23°C, and the room temperature mentioned later regarding the adhesive layer also refers to 23°C. When this layer comes into contact with the adhesive, it adheres to the adhesive through its adhesive force. Adhesion generally refers to the property of exerting adhesive force for a short time after contact with the adhesive with a very light force. In this invention and this specification, the aforementioned "existence of adhesiveness" means that, in the inclined ball adhesion test specified in JIS Z 0237:2009 (testing environment: temperature 23°C, relative humidity 50%), the result is No. 1 to No. 32. When other layers are stacked on the surface of the adhesive layer, for example, the adhesive layer surface exposed by peeling off other layers can be subjected to the above test. When other layers are stacked on one surface and another surface of the adhesive layer respectively, the other layers on either surface side can be peeled off.

[0108] As an adhesive layer, an adhesive layer forming composition comprising adhesives such as acrylic adhesives, rubber adhesives, silicone adhesives, and urethane adhesives can be applied and processed into a thin film.

[0109] The adhesive layer forming composition can be applied to a support, for example. Coating can be performed using known coating equipment such as a doctor blade coater or a die coater. Coating can also be performed in a so-called roll-to-roll manner or in batches.

[0110] Examples of supports for the coating adhesive layer forming composition include films of various resins such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate (PC), polymethyl methacrylate (PMMA), acrylic resins, cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, and polyimide. As a support, a support in which the surface (coated surface) of the coating adhesive layer forming composition has been subjected to a release treatment by a known method can be used. One method of release treatment is forming a release layer. Furthermore, commercially available resin films that have undergone release treatment can also be used as supports. By using a support in which a release treatment has been performed on the coated surface, the adhesive layer and the support can be easily separated at the film thickness.

[0111] An adhesive layer forming composition, in which the adhesive is dissolved and / or dispersed in a solvent, is applied to a metal layer or a high permeability layer and dried, thereby enabling the adhesive layer to be laminated on the surface of the metal layer or the high permeability layer.

[0112] Furthermore, by overlapping and pressurizing the thin-film adhesive layer with the metal layer or the high permeability layer, the adhesive layer can be laminated on the surface of the metal layer or the high permeability layer.

[0113] To manufacture electromagnetic wave shielding materials with adhesive layers, adhesive tapes containing adhesive layers can also be used. Double-sided tapes can be used as adhesive tapes. Double-sided tapes are formed by providing adhesive layers on both sides of a support, and both adhesive layers are adhesive at room temperature. Furthermore, adhesive tapes with adhesive layers on only one side of the support can also be used. Examples of support materials include films, non-woven fabrics, and paper made of various resins such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate (PC), polymethyl methacrylate (PMMA), acrylics, cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, and polyimide. Commercially available adhesive tapes or double-sided tapes manufactured using known methods can be used as adhesive tapes with adhesive layers on one or both sides of the support.

[0114] In this invention and specification, "adhesive layer" refers to a layer that is not tacky at room temperature but exerts adhesive force by being pressed onto an adhesive body while heated, flowing along the minute irregularities of the adhesive body's surface and achieving an anchoring effect; or by being pressed onto an adhesive body while heated, chemically bonding with the surface of the adhesive body through a chemical reaction. The adhesive layer can soften and / or undergo a chemical reaction upon heating. "Not tacky" means that in the tilted ball adhesion test specified in JIS Z0237:2009 (test environment: temperature 23°C, relative humidity 50%), ball No. 1 does not stop. When other layers are stacked on the surface of the adhesive layer, for example, the adhesive layer surface exposed by peeling off other layers can be subjected to the above test. When other layers are stacked on one surface and another surface of the adhesive layer respectively, the other layers on either surface side can be peeled off.

[0115] As an adhesive layer, a thin-film resin material can be used. Thermoplastic resins and / or thermosetting resins can be used as the resin material. Thermoplastic resins have the property of softening upon heating; by pressing them onto the adhesive while heated, they flow, following the minute irregularities on the surface of the adhesive and exerting adhesive force through an anchoring effect; then, by cooling, they can maintain the adhesive state. Thermosetting resins can undergo a chemical reaction upon heating; they can also undergo a chemical reaction by heating in contact with the adhesive, and exert adhesive force by forming a chemical bond with the surface of the adhesive.

[0116] Examples of thermoplastic resins include polyethylene (PE), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), polyvinyl acetate, polyurethane, polyvinyl alcohol, ethylene-vinyl acetate copolymer, styrene-butadiene rubber, acrylonitrile-butadiene rubber, silicone rubber, olefin elastomers (PP), styrene elastomers, ABS resin, polyethylene terephthalate (PET), polyethylene naphthalate (PEN) and other polyesters, polycarbonate (PC), polymethyl methacrylate (PMMA) and other acrylics, cyclic polyolefins, triacetyl cellulose (TAC), etc.

[0117] Examples of thermosetting resins include epoxy resins, phenolic resins, melamine resins, thermosetting urethane resins, xylene resins, and thermosetting silicone resins.

[0118] The adhesive layer contains the same polymer backbone as the resin contained in the high permeability layer, thereby increasing the compatibility between the resin in the high permeability layer and the resin in the adhesive layer. Therefore, this is preferable from the perspective of adhesion between the high permeability layer and the adhesive layer. For example, it is preferable that both the high permeability layer and the adhesive layer contain polyurethane resin.

[0119] The thin-film resin material used as an adhesive layer can be a commercially available product or a thin-film resin material made by known methods.

[0120] In one method, a resin or resin precursor dissolved and / or dispersed in a solvent is coated onto a metal layer or a high permeability layer and cured by drying or overlapping, thereby enabling the deposition of an adhesive layer composed of a thin film resin material on the surface of the metal layer or the high permeability layer.

[0121] Alternatively, a resin or resin precursor dissolved and / or dispersed in a solvent is applied to a support and cured by drying or overlapping, thereby forming an adhesive layer that can be peeled off from the support to form a thin film adhesive layer.

[0122] By superimposing a thin-film adhesive layer with a metal layer or a high-permeability layer and applying pressure under heat, an adhesive layer can be laminated on the surface of a metal layer or a high-permeability layer.

[0123] The high permeability layer, which serves as an adhesive, is heated and pressurized in a state where it overlaps with the adhesive layer of a metal layer on the surface, thereby enabling the metal layer and the high permeability layer to be bonded together via the adhesive layer.

[0124] Alternatively, the metal layer, which acts as an adhesive, is heated and pressurized so that it overlaps with the adhesive layer of a high permeability layer on its surface, thereby allowing the metal layer and the high permeability layer to be bonded together via the adhesive layer.

[0125] Alternatively, the metal layer and the high magnetic permeability layer can be bonded together by placing an adhesive layer of thin-film resin material between these layers and pressing them under heat, thereby bonding the metal layer and the high magnetic permeability layer through the adhesive layer.

[0126] Pressurization under heating can be achieved using flatbed extruders, roll extruders, etc., which have heating mechanisms.

[0127] Furthermore, as an example of an adhesive mechanism, one can cite a double-sided tape described in Japanese Patent Application Publication No. 2003-20453 as a double-sided tape without a silicone-based substrate.

[0128] The conductivity of typical adhesive and bonding layers is extremely low compared to metal layers, and their magnetic permeability is extremely low compared to the aforementioned high-permeability layers. Furthermore, their relative permittivity is only a few times that of air, and their characteristic impedance and propagation constant are similar to those of air. Therefore, using typical adhesive and / or bonding layers will not affect the shielding performance of the shielding material, or the effect is negligible. Regarding adhesive and bonding layers, there are no particular limitations on the thickness of each layer; for example, it can be above 1 μm and below 30 μm.

[0129] In one embodiment, the electromagnetic wave shielding material can be manufactured through one or more of the following processes. However, there are no particular limitations on the manufacturing method of the electromagnetic wave shielding material.

[0130] The bonding of the metal layer and the high magnetic permeability layer is performed using an adhesive layer or bonding layer formed in the form of a thin film.

[0131] The bonding of the metal layer and the high magnetic permeability layer is achieved by forming a high magnetic permeability layer on the surface of which an adhesive layer or bonding layer is provided, and then bonding the high magnetic permeability layer to the metal layer via the adhesive layer or bonding layer.

[0132] The bonding of the metal layer to the high permeability layer is achieved by bonding the metal layer to the high permeability layer via an adhesive layer or bonding layer formed on the surface of the metal layer.

[0133] The adhesive layer or bonding layer is directly applied to the surface of the metal layer or the high permeability layer.

[0134] An adhesive layer or bonding layer is coated on the release film, and after applying pressure and pressing it with a high magnetic permeability layer, or after applying heat and pressure and pressing it with a high magnetic permeability layer, the release film is peeled off, thereby forming a high magnetic permeability layer with an adhesive layer or bonding layer on its surface.

[0135] An adhesive layer or bonding layer is coated on the release film, and after applying pressure to press it against a high magnetic permeability layer, or after applying heat and pressure to press it against a metal layer, the release film is peeled off, thereby forming a metal layer with an adhesive layer or bonding layer on its surface.

[0136] The aforementioned electromagnetic wave shielding material can be of any shape and size, such as a thin film (or sheet). For example, the thin film electromagnetic wave shielding material can be bent into any shape and embedded in electronic components or electronic devices.

[0137] [Electronic Components]

[0138] One aspect of the present invention relates to an electronic component comprising the aforementioned electromagnetic wave shielding material. Examples of such electronic components include those found in mobile phones, mobile information terminals, medical devices, and other electronic devices, as well as semiconductor elements, capacitors, coils, cables, and other electronic components. The electromagnetic wave shielding material can be bent into any shape according to the shape of the electronic component and disposed inside the electronic component, or it can be disposed as a covering material covering the outside of the electronic component. Alternatively, it can be disposed as a covering material processed into a cylindrical shape and used to cover the outside of a cable.

[0139] [Electronic Devices]

[0140] One aspect of the present invention relates to an electronic device comprising the aforementioned electromagnetic wave shielding material. Examples of such electronic devices include mobile phones, mobile information terminals, medical devices, electronic devices comprising various electronic components such as semiconductor elements, capacitors, coils, and cables, and electronic devices in which electronic components are mounted on a circuit board. This electronic device may include the aforementioned electromagnetic wave shielding material as a component of the electronic components included in the device. Furthermore, as a component of the electronic device, the electromagnetic wave shielding material may be disposed inside the electronic device, or may be used as a covering material covering the outside of the electronic device. Alternatively, it may be disposed as a covering material processed into a cylindrical shape and used to cover the outside of a cable.

[0141] As an example of the use of the aforementioned electromagnetic wave shielding material, the use of a semiconductor package coated with a shielding material on a printed circuit board can be cited. For example, "Electromagnetic Wave Shielding Technology in Semiconductor Packages" (Toshiba review Vol. 67 No. 2 (2012) P. 8) discloses a method for obtaining high shielding effect by grounding wiring through side vias at the end of the package substrate and the inner surface of the shielding material when the semiconductor package is coated with a shielding material. For this wiring, the outermost layer of the shielding material on the electronic component side is preferably a metal layer. The aforementioned electromagnetic wave shielding material includes a multilayer structure with one or more layers having the aforementioned high permeability layer between two metal layers. The outermost layer of one or both of the shielding materials can be a metal layer, so it is preferable to use it when performing the wiring as described above.

[0142] Example

[0143] The present invention will now be further described in detail with reference to embodiments. However, the present invention is not limited to the implementation methods shown in the embodiments.

[0144] [Example 1]

[0145] <Preparation of Coating Solution>

[0146] Add to plastic bottles

[0147] Fe-Si-Al flat magnetic particles (MFS-SUH iron-silicon-aluminum alloy manufactured by Marketelytics Solutions India Private Limited) 100g

[0148] 12g of polystyrene-butadiene block copolymer (manufactured by Sigma-Aldrich Japan), 205g of cyclohexanone.

[0149] The coating solution was prepared by mixing with an oscillating stirrer for 1 hour.

[0150] Fabrication of a Magnetic Particle Layer (High Permeability Layer)

[0151] (Film formation containing magnetic particle layers)

[0152] The coating liquid was applied to the release surface of the PET film (PET75TR manufactured by Nippa Corporation, hereinafter also referred to as "release film") that had undergone the release treatment using a doctor blade coater with a coating gap of 300 μm. The film was then dried in a drying apparatus with an internal atmosphere temperature of 80°C for 30 minutes to form a thin film containing magnetic particles.

[0153] (Pressure treatment containing a layer of magnetic particles)

[0154] The upper and lower extrusion plates of a plate extruder (a large hot extruder TA-200-1W manufactured by YAMAMOTO ENG.WORKS Co., LTD.) are heated to 140°C (internal temperature of the extrusion plates). A layer containing magnetic particles from the release film is placed at the center of each release film on the extrusion plate, and an application of 4.66 N / mm is applied. 2 The pressure was maintained for 10 minutes. To maintain the pressure, the upper and lower extrusion plates were cooled to 50°C (internal temperature of the extrusion plates), and then the magnetic particle layer was removed from each peel film.

[0155] <Formation of Shielding Materials>

[0156] A portion of the magnetic particle layer after the peeling of the film is sheared and used as a sample for the following tests: permeability measurement, conductivity measurement, and fracture resistance evaluation. A 5 μm thick double-sided adhesive tape (NeoFix5 S2 manufactured by NEION Film Coatings Corp.) is bonded to the upper and lower surfaces of the magnetic particle layer after shearing, and a 10 μm thick copper foil (compliant with JIS H3100:2018 specification, alloy number C1100R, copper content ≥99.90% by mass) is bonded to the upper and lower surfaces.

[0157] This yielded the electromagnetic wave shielding material of Example 1. The shielding material of Example 1 comprises a multilayer structure of "copper foil / magnetic particle layer (high permeability layer) / copper foil".

[0158] <Determination of magnetic permeability>

[0159] The magnetic particle layer was cut into rectangles measuring 28 mm × 10 mm, and the permeability was measured using a permeability measuring device (PER01 manufactured by KEYCOM Corporation). The permeability was then calculated as the real part (μ') of the complex relative permeability at a frequency of 100 kHz.

[0160] <Determination of Conductivity>

[0161] A cylindrical main electrode with a diameter of 30 mm was connected to the negative side of a digital super-insulation resistance meter (TR-811A manufactured by Takeda Riken Industry Co., Ltd.), and a ring electrode with an inner diameter of 40 mm and an outer diameter of 50 mm was connected to the positive side. The main electrode was placed on a sample containing a magnetic particle layer cut into 60 mm × 60 mm dimensions, and the ring electrode was placed around the main motor. A voltage of 25 V was applied to both electrodes, and the surface resistivity of the magnetic particle layer was measured individually. The conductivity of the magnetic particle layer was calculated from the surface resistivity and the following formula. The thickness of the magnetic particle layer was determined using the method described below.

[0162] Conductivity [S / m] = 1 / (Surface resistivity [Ω] × Thickness [m])

[0163] <Obtaining a cross-sectional image of the shielding material>

[0164] The following method was used to perform profile machining to expose the cross-section of the shielding material.

[0165] The shielding material, cut to 3mm x 3mm dimensions, was embedded in resin, and the cross-section of the shielding material was cut using an ion milling device (IM4000PLUS manufactured by Hitachi High-Tech Co., Ltd.).

[0166] The exposed cross-section of the shielding material was observed using a scanning electron microscope (SU8220 manufactured by Hitachi High-Tech Co., Ltd.) at an accelerating voltage of 2 kV and a magnification of 100x to obtain reflected electron images. From the obtained images, the thicknesses of the magnetic particle layer, each of the two metal layers, and the entire shielding material were measured at five points relative to the scale bar. The arithmetic mean of these measurements was taken as the thickness of the magnetic particle layer, the thickness of each of the two metal layers, and the total thickness of the shielding material.

[0167] <Acquisition of a cross-sectional image of a layer containing magnetic particles (a layer with high magnetic permeability)>

[0168] Similarly, a reflected electron image was obtained by observing a portion of the magnetic particle layer in the cross-section of the shielding material exposed by the machining process using a scanning electron microscope (SU8220 manufactured by Hitachi High-Tech Co., Ltd.) at an accelerating voltage of 2kV and a magnification of 1000x.

[0169] <Determination of aspect ratio of magnetic particles and orientation degree of flat-shaped particles>

[0170] In the reflected electron image obtained above, the aspect ratio of the magnetic particles is determined using the method described above, and the flat-shaped particles are determined by the aspect ratio value. As described above, it is determined whether the magnetic particle layer contains flat-shaped particles as magnetic particles. If it is determined that flat-shaped particles are present, Table 1 states "Contains flat-shaped particles"; if it is determined that flat-shaped particles are not present, Table 1 states "Does not contain". If it is determined that flat-shaped particles are present, the orientation degree of the magnetic particles identified as flat-shaped particles is determined using the method described above. Furthermore, the average aspect ratio (arithmetic mean) of all particles identified as flat-shaped particles is taken as the aspect ratio of the flat-shaped particles contained in the magnetic particle layer.

[0171] <Magnetic particle content of the magnetic particle layer (high permeability layer)>

[0172] The percentage of magnetic particles relative to the total mass of the magnetic particle layer is calculated, and this percentage is taken as the percentage of magnetic particles relative to the total solid content of the coating liquid. Here, the solid content refers to the components in the coating liquid, excluding the solvent, which are magnetic particles and polystyrene-butadiene block copolymer.

[0173] The percentage of magnetic particles relative to the total mass of the magnetic particle layer can also be determined from the total mass of the magnetic particle layer and the mass of magnetic particles cut from the magnetic particle layer using known methods.

[0174] <Evaluation of fracture resistance>

[0175] The sample containing the magnetic particle layer was bent at a right angle and the bent part was observed at 500x magnification using an optical microscope (Nikon Corporation LV150) to confirm whether any breakage had occurred.

[0176] Evaluation of Electromagnetic Wave Shielding Performance (KEC Method)

[0177] A 150mm × 150mm shielding material was placed between the antennas of a KEC method evaluation device, which includes a signal generator, an amplifier, a pair of magnetic or electric field antennas, and a spectrum analyzer. The ratio of the received signal strength without shielding material to the received signal strength with shielding material in the frequency range of 100kHz to 1GHz was calculated as the shielding energy. This was then applied to both the magnetic field antenna and the electric field antenna to determine the shielding energy for magnetic and electric fields.

[0178] <Determination of Bending Width>

[0179] The shielding material was cut into 4cm x 2cm pieces. The cut pieces were folded in half by hand, then unfolded and flattened. The unfolded pieces were attached to a glass slide, and the bent sections were observed using an optical microscope (Nikon Corporation LV150) at 50x magnification to obtain images. In the acquired images, the areas with contrasting brightness compared to the unbent areas were identified as the deformed portions, and their widths were measured. This measured width was taken as the bending width.

[0180] [Example 2]

[0181] When preparing the coating solution, in addition to replacing the polystyrene-polybutadiene block copolymer with...

[0182] 38g of polyurethane resin (UR-8300 manufactured by Toyobo Co., Ltd.) with a solid content of 30% by mass.

[0183] Apart from this, 0.5g of polyfunctional isocyanate (CORONATE L manufactured by TOSOH CORPORATION)

[0184] The electromagnetic wave shielding material was fabricated, and various measurements and evaluations as shown in Tables 1 and 2 were performed using the same method as in Example 1.

[0185] [Example 3]

[0186] Except for setting the amount of cyclohexanone in the coating solution to 300g and the coating gap to 500μm, the electromagnetic wave shielding material was prepared and various measurements and evaluations shown in Tables 1 and 2 were performed in the same manner as in Example 1.

[0187] [Example 4]

[0188] Except for setting the cyclohexanone content of the coating solution to 400g and the coating gap to 600μm, the electromagnetic wave shielding material was prepared and various measurements and evaluations shown in Tables 1 and 2 were performed in the same manner as in Example 1.

[0189] [Example 5]

[0190] Except for the preparation of the coating liquid by the following method, the electromagnetic wave shielding material was made in the same manner as in Example 1, and various measurements and evaluations are shown in Tables 1 and 2.

[0191] Add to plastic bottles

[0192] Iron-based nanocrystalline alloy magnetic particles (KUAMETNC1053C03A manufactured by Epson Atmix Corporation) 75g

[0193] Iron-based amorphous magnetic particles (AW2-08PF-3F manufactured by Epson Atmix Corporation) 25g

[0194] 3.2g of polystyrene-butadiene block copolymer (manufactured by Sigma-Aldrich Japan), 205g of cyclohexanone.

[0195] The coating solution was prepared by mixing with an oscillating stirrer for 1 hour.

[0196] [Example 6]

[0197] When preparing the coating solution, in addition to replacing the polystyrene-polybutadiene block copolymer with...

[0198] Besides the 12g of polybenzyl methacrylate (manufactured by Sigma-Aldrich Japan),

[0199] The electromagnetic wave shielding material was fabricated, and various measurements and evaluations as shown in Tables 1 and 2 were performed using the same method as in Example 1.

[0200] [Example 7]

[0201] When preparing the coating solution, in addition to replacing the polystyrene-polybutadiene block copolymer with...

[0202] Besides the 12g of polymethyl methacrylate (manufactured by Sigma-Aldrich Japan),

[0203] The electromagnetic wave shielding material was fabricated, and various measurements and evaluations as shown in Tables 1 and 2 were performed using the same method as in Example 1.

[0204] [Example 8]

[0205] A magnetic particle layer was fabricated using the same method as in Example 1.

[0206] Using the same copper foil as the copper foil used as the metal layer in Example 1, the five layers of "copper foil / magnetic particle layer / copper foil / magnetic particle layer / copper foil" were bonded together with double-sided tape of the same type used in Example 1. The electromagnetic wave shielding material of Example 8, prepared in this way, was measured and evaluated as shown in Tables 1 and 2 using the same method as in Example 1.

[0207] [Example 9]

[0208] Except for peeling the magnetic particle layer after pressure treatment from the release film and overlapping it into three layers, and then performing pressure treatment again in the same way to thicken the magnetic particle layer, the electromagnetic wave shielding material was manufactured and various measurements and evaluations shown in Tables 1 and 2 were performed in the same way as in Example 8.

[0209] [Example 10]

[0210] Except for changing the thickness of one of the two copper foils to 20 μm, the electromagnetic wave shielding material was fabricated using the same method as in Example 1, and the various measurements and evaluations are shown in Tables 1 and 2.

[0211] [Example 11]

[0212] Except for changing the thickness of one of the two copper foils to 18 μm and the thickness of the other to 2 μm, the electromagnetic wave shielding material was fabricated using the same method as in Example 1, and the various measurements and evaluations are shown in Tables 1 and 2.

[0213] [Example 12]

[0214] Except for replacing the two copper foils with aluminum foils of 15 μm thickness (in accordance with JIS H4160:2006 specifications, alloy number 1N30 quality category (1)0, Al content ≥99.3% by mass), the electromagnetic wave shielding material was manufactured and various measurements and evaluations shown in Tables 1 and 2 were performed in the same manner as in Example 1.

[0215] The shielding material of Example 12 weighed 4.5g when measured at a size of 15cm × 15cm. In contrast, the shielding material of Example 1 weighed 6.7g when measured at the same size.

[0216] [Example 13]

[0217] <Formation of the adhesive layer>

[0218] (Preparation of coating solution)

[0219] Add to plastic bottles

[0220] 100g of 30% by weight polyurethane resin (UR-8300 manufactured by Toyobo Co., Ltd.)

[0221] 900g of methyl ethyl ketone

[0222] The coating solution was prepared by mixing with an oscillating stirrer for 1 hour.

[0223] (Film formation of the adhesive layer)

[0224] The coating liquid was applied to the release surface of the PET film (PET75TR manufactured by Nippa Corporation) after the release treatment was completed using a doctor blade coater with a coating gap of 300 μm. The film was then dried in a drying apparatus with an internal atmosphere temperature of 80°C for 30 minutes, and the adhesive layer corresponding to the adhesive layer described above was formed into a thin film on the release film.

[0225] Two adhesive layers with attached release films were prepared using the above method.

[0226] <Formation of a magnetic particle layer (high permeability layer) with an attached adhesive layer>

[0227] The upper and lower extrusion plates of a plate extruder (a large hot extruder TA-200-1W manufactured by YAMAMOTO ENG.WORKS Co., LTD.) were heated to 140°C (internal temperature of the extrusion plates). The adhesive layer was positioned with the upper surface facing upwards, and an adhesive layer with a release film attached was placed in the center of the extrusion plate. A magnetic particle layer, prepared using the method described in Example 2, was placed on the adhesive layer. The adhesive layer was then positioned with the magnetic particle layer on top of the magnetic particle layer, and the adhesive layer with a release film attached was placed with the lower surface facing upwards. A force of 4.66 N / mm was applied. 2 The pressure was maintained for 10 minutes. To maintain the pressure, the upper and lower extrusion plates were cooled to 50°C (internal temperature of the extrusion plates), and then the magnetic particle layer with double-sided adhesive was removed from each peel film.

[0228] <Formation of Shielding Materials>

[0229] The upper and lower extrusion plates of a plate extrusion press (a large hot extrusion press TA-200-1W manufactured by YAMAMOTO ENG.WORKS Co., LTD.) are heated to 140°C (internal temperature of the extrusion plates). A 10μm thick copper foil (compliant with JIS H3100:2018 specifications, alloy number C1100R, copper content ≥ 99.90% by mass), a magnetic particle layer with a double-sided adhesive layer attached after the release film is peeled off, and another 10μm thick copper foil are applied. A pressure of 4.66 N / mm is then applied. 2 The pressure was maintained for 10 minutes. To maintain the pressure, the upper and lower extrusion plates were cooled to 50°C (internal temperature of the extrusion plates), and then the shielding material was removed by peeling off each film.

[0230] Subsequently, the release film was peeled off to obtain the electromagnetic wave shielding material of Example 13. The shielding material of Example 13 comprises a multilayer structure of "copper foil / magnetic particle layer (high permeability layer) / copper foil". Various measurements and evaluations, as shown in Tables 1 and 2, were performed on the electromagnetic wave shielding material of Example 13.

[0231] [Example 14]

[0232] <Formation of the adhesive layer>

[0233] (Preparation of coating solution)

[0234] Add to plastic bottles

[0235] 100g of 30% by weight polyurethane resin (UR-8300 manufactured by Toyobo Co., Ltd.)

[0236] 900g of methyl ethyl ketone

[0237] The coating solution was prepared by mixing with an oscillating stirrer for 1 hour.

[0238] (Film formation of the adhesive layer)

[0239] The coating liquid is applied to a 10 μm thick copper foil (in accordance with JISH3100:2018 specification, alloy number C1100R, copper content ≥99.90% by mass) using a doctor blade coater with a coating gap of 100 μm. The foil is then dried in a drying apparatus with an internal atmosphere temperature of 80°C for 30 minutes, forming an adhesive layer corresponding to the adhesive layer described above as a thin film on the metal layer.

[0240] Two metal layers with adhesive layers were fabricated using the method described above.

[0241] <Formation of Shielding Materials>

[0242] The upper and lower extrusion plates of a plate extruder (a large hot extruder TA-200-1W manufactured by YAMAMOTO ENG.WORKS Co., LTD.) were heated to 140°C (internal temperature of the extrusion plates). The adhesive layer was positioned with the upper surface facing upwards, and a metal layer with the adhesive layer attached was placed in the center of the extrusion plate. A magnetic particle layer, prepared using the method described in Example 2, was placed on the adhesive layer. The adhesive layer was positioned with the magnetic particle layer on top of it, and the lower surface was faced with the adhesive layer attached, with the metal layer attached to the adhesive layer also placed thereon. A flux of 4.66 N / mm was applied. 2 The pressure was maintained for 10 minutes. To maintain the pressure, the upper and lower extrusion plates were cooled to 50°C (the internal temperature of the extrusion plates) before the shielding material was removed.

[0243] Subsequently, the release film was peeled off to obtain the electromagnetic wave shielding material of Example 14. The shielding material of Example 14 comprises a multilayer structure of "copper foil / magnetic particle layer (high permeability layer) / copper foil". Various measurements and evaluations were performed on the electromagnetic wave shielding material of Example 14, as shown in Tables 1 and 2.

[0244] [Example 15]

[0245] Except that the amount of polystyrene-polybutadiene block copolymer in the coating solution was set to 38g and the amount of cyclohexanone was set to 250g, the electromagnetic wave shielding material was prepared and various measurements and evaluations shown in Tables 1 and 2 were performed in the same manner as in Example 1.

[0246] [Example 16]

[0247] Except that the amount of polystyrene-polybutadiene block copolymer in the coating solution was set to 45g and the amount of cyclohexanone was set to 260g, the electromagnetic wave shielding material was prepared and various measurements and evaluations shown in Tables 1 and 2 were performed in the same manner as in Example 1.

[0248] [Comparative Example 1]

[0249] Except for the preparation of the coating liquid by the following method, the electromagnetic wave shielding material was made in the same manner as in Example 1, and various measurements and evaluations are shown in Tables 1 and 2.

[0250] Add to plastic bottles

[0251] 100g of iron-based amorphous magnetic particles (AW2-08 PF-15F manufactured by Epson Atmix Corporation)

[0252] 3.2g of polystyrene-butadiene block copolymer (manufactured by Sigma-Aldrich Japan), 205g of cyclohexanone.

[0253] The coating solution was prepared by mixing with an oscillating stirrer for 1 hour.

[0254] [Comparative Example 2]

[0255] Except for setting the amount of cyclohexanone in the coating solution to 500g and the coating gap to 800μm, the electromagnetic wave shielding material was prepared and various measurements and evaluations shown in Tables 1 and 2 were performed in the same manner as in Example 1.

[0256] [Comparative Example 3]

[0257] Except for the fact that the metal layer (copper foil) is disposed only on one side of the magnetic particle layer, the electromagnetic wave shielding material was fabricated in the same manner as in Example 1, and the various measurements and evaluations shown in Tables 1 and 2 were performed.

[0258] [Comparative Example 4]

[0259] Except for the method used to prepare the coating liquid, the electromagnetic wave shielding material was prepared using the same method as in Example 1, and various measurements and evaluations are shown in Tables 1 and 2. The layer formed using the following coating liquid is a resin layer that does not contain magnetic particles.

[0260] Add to plastic bottles

[0261] Polystyrene-butadiene block copolymer (manufactured by Sigma-Aldrich Japan) 20g

[0262] Cyclohexanone 205g,

[0263] The coating solution was prepared by mixing with an oscillating stirrer for 1 hour.

[0264] [Comparative Example 5]

[0265] Copper foil (10 μm thick) was used alone as the electromagnetic wave shielding material in Comparative Example 5, and various measurements and evaluations shown in Tables 1 and 2 were performed using the same method as in Example 1.

[0266] [Comparative Example 6]

[0267] Copper foil (20 μm thick) was used alone as the electromagnetic wave shielding material in Comparative Example 6, and various measurements and evaluations shown in Tables 1 and 2 were performed using the same method as in Example 1.

[0268] [Comparative Example 7]

[0269] A magnetic particle layer was fabricated using the same method as in Example 1.

[0270] Using the same copper foil used as the metal layer in Example 1, the three layers of "magnetic particle layer / copper foil / magnetic particle layer" were bonded together with double-sided tape of the same type used in Example 1. The electromagnetic wave shielding material of Comparative Example 7, prepared in this way, was measured and evaluated as shown in Tables 1 and 2 using the same method as in Example 1.

[0271] [Reference Example 1]

[0272] A copper plate (115 μm thick) was used alone as the electromagnetic wave shielding material in Reference Example 1, and various measurements and evaluations shown in Tables 1 and 2 were performed using the same method as in Example 1.

[0273] <Determination of the glass transition temperature (Tg) of resins>

[0274] A sample of the same resin used in the preparation of the coating solution (particulate or powdered) was placed in an aluminum sample pan, sealed by an extruder, and heat flow was measured using a TA Instruments Q100 differential scanning calorimeter under the following conditions. Based on the measurement results, the glass transition temperature of the resin was determined as the baseline offset starting temperature of the heat flow diagram during heating.

[0275] (Measurement conditions)

[0276] Scanning temperature: -80.0℃~200.0℃

[0277] Heating rate: 10.0℃ / minute

[0278] The results are shown in Tables 1 (Tables 1-1 to 1-2) and 2 (Tables 2-1 to 2-2). In Table 1, the columns for electric field shielding energy and magnetic field shielding energy with the additional "above" indicating numerical values ​​indicate that the shielding energy is above the upper limit of the evaluation device used in the KEC method evaluation. Regarding magnetic field shielding energy, it is preferred that the magnetic field shielding energy at 100 kHz is 10.0 dB or more, and the magnetic field shielding energy at 10 MHz is 70.0 dB or more.

[0279]

[0280]

[0281] The results shown in Table 1 confirm that the electromagnetic wave shielding materials of Examples 1-16, which contain an insulating layer (i.e., a high permeability layer) with a real part of complex relative permeability of 30 or more at a frequency of 100 kHz between two metal layers, exhibit excellent shielding performance for both electric and magnetic fields across a wide frequency range from low to high frequencies. In contrast, the electromagnetic wave shielding materials of Comparative Examples 1-7 show lower shielding performance for magnetic fields at 100 kHz and / or 10 MHz in the low-frequency region compared to the electromagnetic wave shielding materials of Examples 1-16. Furthermore, Reference Example 1 illustrates that, in the case of a single metal layer, to obtain high electric and magnetic field shielding performance across a wide frequency range from low to high frequencies, the metal layer must be significantly thicker than the metal layers contained in the electromagnetic wave shielding materials of the examples. However, as shown in Table 2, it is confirmed that with such a thick metal layer, the bending width becomes wider.

[0282] [Table 2-1]

[0283]

[0284] [Table 2-2]

[0285]

[0286] Industrial availability

[0287] One aspect of the present invention is useful in the technical field of various electronic components and various electronic devices.

Claims

1. An electromagnetic wave shielding material comprising a multilayer structure having an insulating layer, i.e., a high permeability layer, between two metal layers, having an insulating layer with a real part of complex relative permeability of 30 or more at a frequency of 100 kHz, wherein the conductivity of the high permeability layer is less than 1 S / m.

2. The electromagnetic wave shielding material according to claim 1, wherein, The high permeability layer contains magnetic particles.

3. The electromagnetic wave shielding material according to claim 2, wherein, The magnetic particles contain metallic particles.

4. The electromagnetic wave shielding material according to claim 2 or 3, wherein, The high permeability layer contains flat-shaped particles as magnetic particles.

5. The electromagnetic wave shielding material according to claim 4, wherein, The sum of the absolute value of the average value of the orientation angles of the flat-shaped particles relative to the surface of the high permeability layer and the variance of the orientation angles, i.e., the degree of orientation, is less than 30°.

6. The electromagnetic wave shielding material according to any one of claims 1 to 3, wherein, The high magnetic permeability layer contains resin.

7. The electromagnetic wave shielding material according to claim 6, wherein, The glass transition temperature (Tg) of the resin is below 50°C.

8. The electromagnetic wave shielding material according to any one of claims 1 to 3, wherein, Let the thickness of one of the two metal layers be T1, and the thickness of the other metal layer be T2. T1 is greater than or equal to T2, and The thickness ratio T2 / T1 is 0.15 or higher.

9. The electromagnetic wave shielding material according to any one of claims 1 to 3, wherein, One or both of the two metal layers are metal layers containing more than 80.0% by mass of metals selected from the group consisting of Al and Mg.

10. The electromagnetic wave shielding material according to any one of claims 1 to 3, wherein, It also includes one or more layers selected from the group consisting of adhesive layers and bonding layers.

11. The electromagnetic wave shielding material according to any one of claims 1 to 3, wherein, The total thickness of the metal layers contained in the electromagnetic wave shielding material is less than 100 μm.

12. The electromagnetic wave shielding material according to any one of claims 1 to 3, wherein, The total thickness of the electromagnetic wave shielding material is less than 200 μm.

13. An electronic component comprising the electromagnetic wave shielding material according to any one of claims 1 to 12.

14. An electronic device comprising the electromagnetic wave shielding material according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • Shield material

    JP1991006898A

  • Silicon-based substrate-free double-coated tape and method for using the same tape

    JP2003020453A

  • Adhesive film

    JP2015187260A

  • Soft magnetic flat powder

    JP2018131640A

  • Electromagnetic wave shielding material with high-conductivity metal layer

    CN103796497A